Autofluorescence imaging in the differential diagnosis of optic disc melanocytoma. (28th April 2015) - Salvanos, Panagiotis; Utheim, Tor P.; Moe, Morten C.; Eide, Nils; Bragadόttir, Ragnheiður
Abstract Purpose Optic disc melanocytoma (ODM) is a benign tumour that usually occurs on or adjacent to the optic nerve head. The aim of the study was to evaluate fundus autofluorescence (FAF) imaging as a diagnostic tool in ODM. Methods Retrospective comparative case series study of six patients with ODM and a comparing group of four patients with juxtapapillary choroidal nevus (JCN) and four with juxtapapillary uveal melanoma (JUM). Clinical examination was supplemented with ultrasound B‐scan examination and spectral‐domain optical coherence tomography. FAF images were obtained with the 532‐nm laser (Optomap P200Tx) from all patients. Results Clinical examination in the ODM group revealed a dome‐shaped, darkly pigmented tumour on or adjacent to the optic disc in all patients, with a mean tumour basal dimension 1.4 mm and mean tumour thickness by ultrasonography of 1.0 mm. FAF revealed a totally hypofluorescent mass with sharply demarcated, feathery edges. No hyperfluorescent changes due to orange pigment or subretinal fluid were seen. In contrast, patients with JCN and JUM manifested focal hyperfluorescence as well as larger hyperfluorescent areas at the tumour and its borders. Conclusion Fundus autofluorescence imaging is a non‐invasive adjuvant tool in the differential diagnosis of ODM characterized by lack of hyperfluorescence compared to JCN and JUM.